2021
DOI: 10.1021/acscentsci.1c00633
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanocomposite Membranes with Ultrahigh Ion Selectivity for Osmotic Power Conversion

Abstract: Ion transport in nanoconfinement exhibits significant features such as ionic rectification, ionic selectivity, and ionic gating properties, leading to the potential applications in desalination, water treatment, and energy conversion. Two-dimensional nanofluidics provide platforms to utilize this phenomenon for capturing osmotic energy. However, it is challenging to further improve the power output with inadequate charge density. Here we demonstrate a feasible strategy by employing Kevlar nanofiber as space ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 47 publications
0
52
0
Order By: Relevance
“…69–72 Therefore, a number of chemical engineering applications with CCE in nanochannels are being reported, which cover the research fields of energy conversion and the environment. 33,34,73,74…”
Section: Chemical Engineering With Cce In Nanochannelsmentioning
confidence: 99%
“…69–72 Therefore, a number of chemical engineering applications with CCE in nanochannels are being reported, which cover the research fields of energy conversion and the environment. 33,34,73,74…”
Section: Chemical Engineering With Cce In Nanochannelsmentioning
confidence: 99%
“…To optimize large-scale implementation of RED or blue energy technology using membranes, as a top-down approach, multiple compartment RED cells have been constructed [28,56,57]. Recent studies have shown several crucial influences of ion-exchange membranes [3,58,59] of different materials (e.g., microfiltration [60], polymeric [15,61,62], graphene [18,20], Nafion [13,63]), surface charges, and pore-size distributions, electrolyte solutions (e.g., types of ions [64][65][66], multivalent ions [67], ion concentrations), as well as hydrodynamics affected by the flow configurations [68] and cell designs through separators' dimensions [23][24][25][26]. Typical power density outputs measured with various ion exchange membrane stacks ranged from 0.13 to 2.48 W m −2 [32].…”
Section: Introductionmentioning
confidence: 99%
“…In their latest pioneering work published in this issue of ACS Central Science, Liping Wen et al highlight the promise of biomimetic nacrelike design as nanofluidic devices for selective ion transport and sustainable energy conversion. 1 Ion transport regulated by ion channels plays a foundational role in the physiological activities of live beings, such as sensing, energy conversion, and information transmission. 2−4 Artificial ion channels with nanoscale confined spaces are expected to be an ideal model for exploring future nanofluidic devices.…”
mentioning
confidence: 99%
“…In this work, 1 Liping Wen and the team drew inspiration from nature when approaching their materials design, and introduced one dimensional (1D) charged aramid nanofibers (ANFs) into 2D graphene oxide (GO) nanosheets (Figure 1). To overcome the instability of the layered system, Wen et al took inspiration from the natural nacrelike "brickand-mortar" structure and constructed GO/ANF membranes with hard GO nanosheets as the "brick" and soft ANFs as the "mortar", which represent a robust nanofluidic system with superior structural stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation